Leviathan and Competition among Jurisdictions: The Case of Benefit Taxation - Michael Rauscher (Universität Rostock, Institut für Volkswirtschaftslehre, 1997)
The paper shows that interjurisdictional competition for mobile factors of production forces the government to raise the efficiency of the public sector and, thus, helps to tame Leviathan governments. However, this result is derived under some restrictive assumptions concerning the kind of tax policy used by the government. In the case of benefit taxes, e.g. user charges, a Leviathan may be tamed by interjurisdictional competition whereas this is not necessarily true in the case of lum-sum taxes.
Keywords: F20; H21; H40; H73; 330